Public private : a fundamental research of Public Sector Comparator (PSC) as an evaluation tool for Value For Money (VFM) ASSESSMEN / Dr Roshana Takim, Dr Intan Rohani Endut and Kharizam Ismail - Takim, Roshana; Endut, Intan Rohani; Ismail, Kharizam (Research Management Institute (RMI), 2011)
Globally, Public Private Partnership (PPP) is seen as an effective way to achieve value for money (VFM) in delivering of public projects. VFM is the term used to assess whether the organisation has obtained the maximum benefit from the goods and services it acquires over the whole life of a project. Principally, VFM will be determined through the evaluation of financial and non-financial aspects to assess a range of project outcomes. It is usually associated with utilising innovative capabilities and skills, efficiency savings, fitness for purpose and best possible risk transfer to private sector. In order to assess whether a PPP proposed project is the optimal solution, it is necessary to determine whether it provides the best VFM outcome. The achievement of a VFM outcome is a crucial concept throughout the procurement process in all aspects of the project. Assessing the value of these variables requires a degree of judgment and the use of both quantitative and qualitative analysis…